2022
DOI: 10.1515/bmt-2021-0265
|View full text |Cite
|
Sign up to set email alerts
|

Smart piezoelectric biomaterials for tissue engineering and regenerative medicine: a review

Abstract: Due to the presence of electric fields and piezoelectricity in various living tissues, piezoelectric materials have been incorporated into biomedical applications especially for tissue regeneration. The piezoelectric scaffolds can perfectly mimic the environment of natural tissues. The ability of scaffolds which have been made from piezoelectric materials in promoting cell proliferation and regeneration of damaged tissues has encouraged researchers in biomedical areas to work on various piezoelectric materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 155 publications
0
23
0
Order By: Relevance
“…These devices are capable of utilizing biomechanical movements such as muscle motions, lungs motion, or blood circulation to convert into electrical power output [16,17]. The piezoelectric effect is one of the techniques utilized to convert the mechanical energy into electrical power at a particular frequency range [18,19]. However, such EHs have limited applications because of their bulkiness, which restricts their contact with furrowed and undulated body surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…These devices are capable of utilizing biomechanical movements such as muscle motions, lungs motion, or blood circulation to convert into electrical power output [16,17]. The piezoelectric effect is one of the techniques utilized to convert the mechanical energy into electrical power at a particular frequency range [18,19]. However, such EHs have limited applications because of their bulkiness, which restricts their contact with furrowed and undulated body surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…6 In the last researches, it has been observed that the contribution of the localized electric charge produced by piezoelectric materials to the healing process of damaged tissues is crucial. [7][8][9] Wireless piezoelectric stimulation mediated by piezoelectric biomaterials has recently been proposed as an innovative approach in which electrical cues are localized and externally stimulated with a wireless external stimulus such as ultrasound (U/S), and this approach can potentially overcome the limitations of current electrical stimulation procedures. 10,11 U/S is commonly applied in medicine for diagnostic applications, 12 in which they are utilized to trigger tissue devastation or repair by inducing mechanical effects at the target site.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] In addition, the stability of pH during the biodegradation process of PHB distinguishes it from other biodegradable aliphatic esteric polymers such as poly (ε-caprolactone) (PCL), poly(lactic acid) (PLA). 29 However, the piezoelectric response of biodegradable PHB is substantially lower compared to other known piezoelectric materials such as non-biodegradable polyvinylidene fluoride and its copolymers or piezoelectric ceramics 9,30 and PHB electrospun scaffolds, on the other hand, inhibit cellular activities such as cell adhesion, proliferation, and growth due to their hydrophobic nature. 31 Therefore, it is necessary to improve the piezoelectric properties and wettability of PHB-based piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of functional and smart biomaterials has emerged the multidisciplinary subjects including medicine, biology, physics, chemistry and materials science, etc., and is playing important role in clinical applications, e.g., facilitating wound healing and restoring other types of biological function ( Freudenberg et al, 2016 ; Shodeinde et al, 2020 ; Najjari et al, 2022 ). However, the performance of these biomaterials still need to be further enhanced due to the complicated interactions with components of living systems and the unpredictable responses of body to biomaterials ( Kowalski et al, 2018 ).…”
mentioning
confidence: 99%